Studi Komparasi Pemberian Rebusan Kayu Manis dan Daun Kelor terhadap Penurunan Tekanan Darah pada Penderita Hipertensi - Iskandar, Iskandar; Afriana, Fira Nur; Tharida, Maimun; Yullyzar, Yullyzar (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Hypertension is a non-communicable disease that is one of the public health problems and is often referred to as a silent killer because it is a disease that can cause sudden death. This disease often does not cause symptoms and can cause complications over a long period of time. One of the herbal drinks that can lower blood pressure in people with hypertension is cinnamon and moringa leaf tea. The purpose of this study was to determine the effect of a comparative study of the administration of cinnamon decoction and Moringa leaves on lowering blood pressure in patients with hypertension. The research design is a comparative study with a two group pretest posttest design approach. The population in this study were all hypertensive patients as many as 41 people and a sample size of 30 people with purposive sampling technique. Data collection instruments use observation sheets. This research was conducted in Ceurih Village Ulee Kareng District Banda Aceh City from May 1 to 15, 2025. Data analysis using paired and independent sample t-tests. The results showed that there was an effect before and after giving cinnamon decoction on blood pressure reduction (p-value = 0.000) and there was an effect before and after giving moringa leaf decoction on blood pressure reduction (p-value = 0.000). Then there is a difference between the administration of cinnamon and moringa leaf decoction on blood pressure reduction (p-value = 0.010). The conclusion of this study is that there is an effect of giving a decoction of cinnamon and moringa leaves on lowering blood pressure in patients with hypertension.